Exotic plant species are locally adapted but not to high ultraviolet‐B radiation: a reciprocal multispecies experiment. Issue 5 (8th April 2019) - Hock, Maria; Hofmann, Rainer W.; Müller, Caroline; Erfmeier, Alexandra
Abstract: Ultraviolet (UV) radiation intensities differ among global regions, with significantly higher levels in the southern hemisphere. UV‐B may act as an environmental filter during plant invasions, which might particularly apply to plant species from Europe introduced to New Zealand. Just like for any other abiotic or biotic filter, successful invaders can cope with novel environmental conditions via plastic responses and/or through rapid adaptation by natural selection in the exotic range. We conducted a multispecies experiment with herbaceous plants in two common gardens located in the species' native and exotic ranges, in Germany and New Zealand, respectively. We used plants of German and New Zealand origin of eight species to test for adaptation to higher UV‐B radiation in their new range. In each common garden, all plants were exposed to three radiation treatments: (1) ambient sunlight, (2) exclusion of UV‐B while transmitting ambient UV‐A, and (3) combined exclusion of UV‐B and UV‐A. Linear mixed‐effect models revealed significant effects of UV‐B on growth and leaf traits and an indication for UV‐B‐induced biomass reduction in both common gardens pointing to an impact of natural, ambient UV radiation intensities experienced by plants in the northern and in the southern hemisphere. In both common gardens, the respective local plants (i.e., German origins in Germany, New Zealand origins in New Zealand) displayed enhanced productivity and aboveground biomass allocation, thus providing evidence for recent evolutionary processes in the exotic range. Genetic differentiation between different origins in consequence of divergent local selection pressures was found for specific leaf area. This differentiation particularly hints at different selective forces in both ranges while only little evidence was found for an immediate selective effect of high UV‐B intensities in the exotic range. However, reaction norm slopes across ranges revealed higher plasticity of exotic individuals in functional leaf traits that might allow for a more sensitive regulation of photoprotection measures in response to UV‐B. During the colonization, New Zealand populations might have been selected for the observed higher phenotypic plasticity and a consequently increased ability to successfully spread in the exotic range.